Bluish : a novel - Hamilton, Virginia, 1936-2002. (New York, NY : Scholastic Inc., 1999)
Ten-year-old Dreenie feels both intrigued and frightened when she thinks about the girl nicknamed Bluish, whose leukemia is making her pale and causing her to use a wheelchair.
G2
Keywords: Leukemia -- Fiction; Wheelchairs -- Fiction; People with disabilities -- Fiction; Schools -- Fiction; African Americans -- Fiction; New York (N.Y.) -- Fiction